Strategi Pengembangan Sumber Daya Manusia Pegawai: Studi pada Kelurahan Gunung Terang, Kota Bandar Lampung - Gaol, Rotua Astrina Lumban; Pradana, Kenny Candra; Tiarni, Ajeng (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the human resource development (HRD) strategies implemented at the Gunung Terang Village Office, Bandar Lampung City, and to assess their contribution to improving employee professionalism and the quality of public services. A qualitative descriptive method was employed, with data collected through observation, in-depth interviews, and documentation involving all village office employees. The findings reveal that HRD practices at the village office are limited to short-term technical training without support for structured formal education or a competency-based career development system. Although the training provided is relevant to employees’ tasks, it is conducted incidentally and lacks long-term planning, while job promotions are predominantly based on seniority due to the absence of a merit-based system. These conditions create a gap between HRD needs and the strategies currently implemented, resulting in limited strategic impact on bureaucratic quality improvement. This study recommends the formulation of a structured, sustainable HRD strategy grounded in needs analysis to ensure equal access to competency enhancement and to strengthen professionalism among village office personnel.